Palladium catalyst immobilized on functionalized microporous organic polymers for C–C coupling reactions. Issue 59 (28th October 2019) - Xu, Wei; Liu, Cijie; Xiang, Dexuan; Luo, Qionglin; Shu, You; Lin, Hongwei; Hu, Yangjian; Zhang, Zaixing; Ouyang, Yuejun
Abstract : Two microporous organic polymers were prepared from 1, 10-phenanthroline by Scholl coupling reaction and Friedel–Crafts reaction, and applied to Heck reaction and Suzuki–Miyaura reaction as heterogeneous catalysts. Abstract : Two microporous organic polymer immobilized palladium (MOP-Pd) catalysts were prepared from benzene and 1, 10-phenanthroline by Scholl coupling reaction and Friedel–Crafts reaction, respectively. The structure and composition of the catalyst were characterized by FT-IR, TGA, N2 sorption, SEM, TEM, ICP-AES and XPS. MOP-Pd catalysts were found to possess high specific surface areas, large pore volume and low skeletal bone density. Moreover, the immobilized catalyst also had advantages, such as readily available raw materials, chemical and thermal stability, and low synthetic cost. The Pd catalyst is an effective heterogeneous catalyst for carbon–carbon (C–C) coupling reactions, such as the Heck reaction and Suzuki–Miyaura reaction, affording good to high yields. In these reactions, the catalyst was easily recovered and reused five times without significant activity loss.